Creating a space for strangers - Kirsty Hamilton; Kathleen Mulvey (Scottish Journal of Residential Child Care, 2010)
For those of you fortunate enough to have experienced a SIRCC annual conference then you will also know that it is an opportunity for so much more than experiential workshops and guest speakers. It is an opportunity for people from all across the residential child care sector to come together, share their knowledge and practice and support each other on the journey.